Agile Information Business Exploring Managerial Implications (Flexible Systems Management,, 2018)
This book accomplishes an analysis of critical aspects of managerial implications on the business with information. The business dealing with information is spreading in the service market; and, an efficient management of informational processes, in order to perform successful business with them, is now crucial. Besides, economical/business, technological or any other kind of information, organized in a variety of forms, can be considered as an 'informational product'. Thus, creating a business value out of information is challenging but vital, especially in the modern digital age. Accordingly, the book covers the methods and technologies to capture, integrate, analyze, mine, interpret and visualize information out of distributed data, which in turn can help to manage information competently. This volume explores the challenges being faced and opportunities to look out for in this research area, while discussing different aspects of this subject. The book will be of interest to those working in or are interested in joining interdisciplinary and transdisciplinary work in the areas of information management, service management, and service business. It will also be of use to young generation researchers by giving them an overview on different aspects of doing business with information. While introducing them to both technical and non-technical details, as well as economic aspects, the book will also be extremely informative for professionals who want to understand and realize the potential of using the cutting-edge managerial technologies for doing successful business with information/ services.